Analisis APBD Perspektif Islamic Human Development Index Kota Bogor Tahun 2021 - Shalahuddin, Hizbi (As-Syirkah: Islamic Economic & Financial Journal, 2023)
I-HDI stands for Islamic Human Development Index which is used as a measuring tool for human development in an Islamic perspective. In formulating the I-HDI, the guidelines for the objectives of sharia or maqashid sharia are used as an indicator of human needs both materially and spiritually. The purpose of this study is to describe the budget for health, education and economics from the perspective of the Islamic Human Development Index in the Bogor City in 2021 . The research method used is descriptive quantitative. Based on the regional government program of the Bogor City, the results show that the health, education and economic budgets are in line with the objectives of the I-HDI. The highest budget is occupied by the education budget of Rp 492.984.200.958, health budget of Rp. 289.239.714.720 and an economic budget of Rp. 82.369.922.609. Then for the results of the I-HDI calculation, each index gets an average value for five years. The ad Dien index is 0,778 the an Nafs index is 0.828, the al 'aql index is 0,642 the Nasl index is 2.815 and the al Maal index is 4.29. From these results, there are several aspects in the execution of the program that have not been carried out optimally. So that it has an impact on the lack of I-HDI numbers on the al aql index and the Nafs index.e